EFFECT OF HEAVY METAL POLLUTION ON FUNGAL DIVERSITY IN SOIL AROUND INDUSTRIAL AREAS OF MYSORE, KARNATAKA - M.S.RAKESH SHARMA; N.S.RAJU (International Journal of Pharma and Bio Sciences, 2013)
The present study was focused on the microbial community of soil collected from industrial areas of Mysore district. The collected soil samples from industrial areas were analyzed for pH, Temperature, Electrical conductivity, Moisture content, Water holding capacity and heavy metal analysis such as Iron (Fe), Copper (Cu), Zinc (Zn), Nickel (Ni), Chromium (Cr) Lead (Pb), and Cadmium (Cd) and by AAS method. Physiochemical analysis was revealed that the pH from 5.82 to 6.90, temperature from 26 to 31oC, EC from 45.4 to 197.8µmho/cm, moisture content from 2.45 to 3.72 percent, water holding capacity varies from 30 to 45 percent. This study was navigated to isolate the microorganisms from heavy metal contaminated site. The Iron (Fe) content were ranged between 1.96 to 3.88g/kg, Copper (Cu) content was ranging from 45 to 63mg/kg, Zinc (Zn) content varies from 35 to 58mg/kg, Nickel (Ni) content is ranging from 9.8 to 14.6mg/kg, Chromium (Cr) content is ranging from 3.8 to 13.8mg/kg. It has been found that Lead (Pb) and Cadmium (Cd) concentrations were low in most of the samples of the study area. The fungal species were identified as Aspergillus sp., Fusarium sp., Penicillium sp., Rhizopus sp., and Curvularia sp., in all the soil samples. Among all the species Aspergillus sp.,are more dominant in all soil samples of the study area.